Keynote: Going to university - Blended strategies for learning and teaching in a modern tertiary context - Dianne Forbes (Flexible Learning Association of New Zealand, 2016)
This 'thinkpiece' is a follow up to the keynote talk delivered at the biannual DEANZ Conference, at the University of Waikato in Hamilton, New Zealand in April 2016. It explores Mixed Media Pathways: Bringing teacher education to your home town. Starting by pondering my own experiences as a tertiary student, I consider some of the changes and challenges facing universities today, and pose one response to these changes in the form of blended learning. The Bachelor of Teaching, Mixed Media Presentation (MMP), an initial teacher education degree at the University of Waikato, is used to illustrate the benefits and challenges of blended learning, for students and lecturers. It is proposed that students based on campus can benefit from blended learning, just as geographically dispersed students can. Going to university can be about active learning partnerships across a range of physical locations.